THE WORK ENVIRONMENT, COMPETENCIES, LEADERSHIP STYLE ON THE PERFORMANCE OF PUBLIC ELEMENTARY SCHOOL TEACHERS IN THE EAST SEMENDAWAI DISTRICT - Yoyon Dwi Wahyono; Fatimah Fatimah; Zunaidah Zunaidah (KOLEGIAL, 2020)
The purpose of this study was to determine and analyze the influence of the work environment, competencies, leadership style on the performance of public elementary school teachers in the East Semendawai District. The population usedin this study were all teachers of public elementary school in the East Semendawai District with a total sample of 180 teachers. The researh method used is an associative analysis method using path analysis, and the operation of its calculations using the application program version 16.0. The results of this study are as follows: 1) The work environment, competence, leadership style together have a significant effect on job satisfaction of teachers of public elementary school in the East Semendawai District. 2) The work environment, leadership style and job satisfaction together have a significant affect on the performance of public elementary school teachers in the East Semendawai District. 3) The work environment did not have a significant effect and negative on job satisfaction of public elementary school teachers in East Semendawai District. 4) Competence has a significant effect and positive on job satisfaction of public elementary school teachers in East Semendawai District. 5) Leadership style has a significant effect and positive on job satisfaction of public elementary school teachers in East Semendawai District. 6) The work environment did not have a significant effect and negative on the performance of public elementary school teachers in East Semendawai District. 7) leadership style has a significant positive effect on the performance of public elementary school teachers in East Semendawai District. 8) Job satisfaction did not have a significant effect and positif on teacher performance of public elementary school teachers in East Semendawai District.